2014
DOI: 10.4172/2252-5211.1000165
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Study of the Release of BTEX from Asphalt Modified with Used Motor Oil and Crumb Rubber Modifier

Abstract: The need to be more environmentally conscious has recently shifted toward the forefront of society. With this new focus on environmentally responsible behavior comes the practice of using recycled materials in construction when possible. Therefore it is necessary to carefully evaluate the safety of any recycled materials being used in pavement materials. Under this study, a reference of testing is presented and implemented to test leachate of samples of two different asphalt binder types containing used motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Interestingly, a lower increase in BTEX concentrations was noted for samples modified with CRM-UMO than only CRM. This illustrates the ability of the CRM to absorb UMO and release its BTEX components slowly; this is in agreement with another study that reported samples modified by CRM-UMO had lower BTEX concentrations than samples modified with UMO only [15]. It can be inferred that toluene had the highest concentrations in both modified asphalt binders, while o-xylene had the lowest concentrations.…”
Section: Portable Gas Chromatography Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Interestingly, a lower increase in BTEX concentrations was noted for samples modified with CRM-UMO than only CRM. This illustrates the ability of the CRM to absorb UMO and release its BTEX components slowly; this is in agreement with another study that reported samples modified by CRM-UMO had lower BTEX concentrations than samples modified with UMO only [15]. It can be inferred that toluene had the highest concentrations in both modified asphalt binders, while o-xylene had the lowest concentrations.…”
Section: Portable Gas Chromatography Resultssupporting
confidence: 91%
“…Recycling 2019, 4 18 concentrations than samples modified with UMO only [15]. It can be inferred that toluene had the highest concentrations in both modified asphalt binders, while o-xylene had the lowest concentrations.…”
Section: Portable Gas Chromatography Resultsmentioning
confidence: 94%
See 3 more Smart Citations